Targeting Tumor-Associated Antigen: A Promising CAR-T Therapeutic Strategy for Glioblastoma Treatment - Zhu, Guidong; Zhang, Qing; Zhang, Junwen; Liu, Fusheng (Frontiers in Pharmacology, 2021)
Chimeric antigen receptor T cells (CAR-T) therapy is a prospective therapeutic strategy for blood cancers tumor, especially leukemia, but it is not effective for solid tumors. Glioblastoma (GBM) is a highly immunosuppressive and deadly malignant tumor with poor responses to immunotherapies. Although CAR-T therapeutic strategies were used for glioma in preclinical trials, the current proliferation activity of CAR-T is not sufficient, and malignant glioma usually recruit immunosuppressive cells to form a tumor microenvironment that hinders CAR-T infiltration, depletes CAR-T, and impairs their efficacy. Moreover, specific environments such as hypoxia and nutritional deficiency can hinder the killing effect of CAR-T, limiting their therapeutic effect. The normal brain lack lymphocytes, but CAR-T usually can recognize specific antigens and regulate the tumor immune microenvironment to increase and decrease pro- and anti-inflammatory factors, respectively. This increases the number of T cells and ultimately enhances anti-tumor effects. CAR-T therapy has become an indispensable modality for glioma due to the specific tumor-associated antigens (TAAs). This review describes the characteristics of CAR-T specific antigen recognition and changing tumor immune microenvironment, as well as ongoing research into CAR-T therapy targeting TAAs in GBM and their potential clinical application.